Unraveling the epigenetic fabric of type 2 diabetes mellitus: pathogenic mechanisms and therapeutic implications - Jazieh, Cham; Arabi, Tarek Ziad; Asim, Zohaib; Sabbah, Belal Nedal; Alsaud, Aljohara Waleed; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Endocrinology, 2024)
Type 2 diabetes mellitus (T2DM) is a rapidly escalating global health concern, with its prevalence projected to increase significantly in the near future. This review delves into the intricate role of epigenetic modifications -including DNA methylation, histone acetylation, and micro-ribonucleic acid (miRNA) expression -in the pathogenesis and progression of T2DM. We critically examine how these epigenetic changes contribute to the onset and exacerbation of T2DM by influencing key pathogenic processes such as obesity, insulin resistance, β-cell dysfunction, cellular senescence, and mitochondrial dysfunction. Furthermore, we explore the involvement of epigenetic dysregulation in T2DM-associated complications, including diabetic retinopathy, atherosclerosis, neuropathy, and cardiomyopathy. This review highlights recent studies that underscore the diagnostic and therapeutic potential of targeting epigenetic modifications in T2DM. We also provide an overview of the impact of lifestyle factors such as exercise and diet on the epigenetic landscape of T2DM, underscoring their relevance in disease management. Our synthesis of the current literature aims to illuminate the complex epigenetic underpinnings of T2DM, offering insights into novel preventative and therapeutic strategies that could revolutionize its management.